The Effect of Shooting by Petanque Athletes of Bima Regency on the Achievement of Provincial Sports Week - Irfan; Nasrullah; Yanti, Sri (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aimed to determine the extent to which the effect of shooting training using obstacles on athletes of the Petanque Training Center (TC) of Bima Regency could improve performance at the NTB Provincial Sports Week in 2023. Materials and methods. This research was a pseudo-experimental study with a "one group pretest and posttest design". The research instrument for petanque athletes was a pretest shooting at a distance of 8 meters, while the treatment was shooting practice using obstacles at distances 6, 7, 8, and 9 and throwing bosi at a distance of 10 throws each. The posttest was conducted to measure the ability of petanque athletes to shoot at a distance of 8 meters. The subjects in this study were Bima Regency petanque athletes who participated in the 2023 NTB Provincial Sports Week TC, totaling 10 people. Results. Based on the t-test statistical test, the pretest shooting results were obtained with an average value of 9.70, while the post-test shooting results with an average value of 16.10, with an average difference of 6.400. The final result of the T-Test obtained a significance value of <0.001, with a significance level of 0.05. Conclusion. There was an influence of shooting practice using obstacles on the performance of Bima Regency petanque athletes, this was evidenced by the achievement of winning 6 medals at the NTB Provincial Sports Week championship in 2023. However, in this study, shooting practice is not the only variable that affects the performance of petanque athletes.